Negative electron transfer dissociation sequencing of 3-O-sulfation containing heparan sulfate oligosaccharides - Wu, Jiandong (J Am Soc Mass Spectrom, 2018)
Among dissociation methods, negative electron transfer dissociation (NETD) has proven the most useful for glycosaminoglycan (GAG) sequencing because it produces informative fragmentation, a low degree of sulfate losses, high sensitivity, and translatability to multiple instrument types. The challenge, however, is to distinguish positional sulfation. In particular, NETD has been reported to fail to differentiate 4-O- versus 6-O-sulfation in chondroitin sulfate decasaccharide. This raised the concern of whether NETD is able to differentiate the rare 3-O-sulfation from predominant 6-O-sulfation in heparan sulfate (HS) oligosaccharides. Here we report that NETD generates highly informative spectra that differentiate sites of O-sulfation on glucosamine residues, enabling structural characterizations of synthetic HS isomers containing 3-O-sulfation. Further, lyase-resistant 3-O-sulfated tetrasaccharides from natural sources were successfully sequenced. Notably, for all of the oligosaccharides in this study, the successful sequencing is based on NETD tandem mass spectra of commonly observed deprotonated precursor ions without derivatization or metal cation adduction, simplifying the experimental workflow and data interpretation. These results demonstrate the potential of NETD as a sensitive analytical tool for detailed, high-throughput structural analysis of highly sulfated GAGs.